2017
DOI: 10.1016/j.bmc.2017.10.039
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification and in vivo characterization of small molecule therapeutic hypothermia mimetics

Abstract: Hypothermia has been proved to have a beneficial effect on several pathologies. CIRBP is one of the so termed cold-shock proteins involved in this process. In this work, we have detected small molecules capable of modulating the activity of CIRBP in the absence of a cold stimulus, by High Throughput Virtual Screening (HTVS) of the Diversity Set IV of the NCI and 15 compounds of our in-house data base. Fifteen compounds were selected from the HTVS to carry out a second screening through a cell-based Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 41 publications
0
23
1
Order By: Relevance
“…There are several promising therapies to target CIRBP in vivo . Coderch et al (2017) identified the first small-molecule CIRBP inducers. A single IP bolus of compound Zr17-2 (∼6.5 μg/kg) increased CIRBP levels in the lung and in the pancreas 4 days later in normothermic rats and CIRBP levels modestly increased in the cerebral cortex.…”
Section: Induction Of Csps During Cold Stress: Potential Applicationsmentioning
confidence: 99%
“…There are several promising therapies to target CIRBP in vivo . Coderch et al (2017) identified the first small-molecule CIRBP inducers. A single IP bolus of compound Zr17-2 (∼6.5 μg/kg) increased CIRBP levels in the lung and in the pancreas 4 days later in normothermic rats and CIRBP levels modestly increased in the cerebral cortex.…”
Section: Induction Of Csps During Cold Stress: Potential Applicationsmentioning
confidence: 99%
“…Such a compound could serve to treat acute brain injury and chronic disease. A preliminary successful example has already been developed with the CIRP homologue, although its activity requires further tests 42 . In addition, the safety of RBM3-based therapy will need to be carefully evaluated for potential tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Zr17‐2 was a first synthesized CIRBP agonist which was reported to be capable of modulating the activity of CIRBP even in the absence of a cold stimulus 8 . It is a small molecule that interacts simultaneously with the flexible part of CIRBP and the RNA‐binding site to inhibit degradation of CIRBP by protease, thus maintaining its active form.…”
Section: Discussionmentioning
confidence: 99%
“…Zr17-2 was a first synthesized CIRBP agonist which was reported to be capable of modulating the activity of CIRBP even in the absence of a cold stimulus. 8 It is a small molecule that interacts simultaneously with the flexible part of CIRBP and the RNA-binding site to inhibit degradation of CIRBP by protease, thus maintaining its active form. In this study, we found Zr17-2-blocked CIRBP degradation in cardiomyocytes to preserve the active protein and its functions for longer periods of time, thereby enhancing CoQ 10 biosynthesis to protect cardiomyocytes against oxidative stress and promote ATP production during extended heart preservation.…”
Section: E417mentioning
confidence: 99%
See 1 more Smart Citation